2020
DOI: 10.1093/femsec/fiaa079
|View full text |Cite
|
Sign up to set email alerts
|

Effect of stevia on the gut microbiota and glucose tolerance in a murine model of diet-induced obesity

Abstract: Artificial sweeteners have been shown to induce glucose intolerance by altering the gut microbiota; however, little is known about the effect of stevia. Here, we investigate whether stevia supplementation induces glucose intolerance by altering the gut microbiota in mice, hypothesizing that stevia would correct high fat diet-induced glucose intolerance and alter the gut microbiota. Mice were split into four treatment groups: low fat, high fat, high fat + saccharin and high fat + stevia. After 10 weeks of treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 72 publications
3
17
1
2
Order By: Relevance
“…Conversely, in recent years, the effect of non-caloric sweeteners on the regulation of glucose levels has also been evaluated. The results to date are controversial, finding that some artificial sweeteners induce glucose intolerance (37). This may be due to the type of noncaloric sweetener consumed, its absorption and transport in the small and large intestines, as well as shifts in gut microbiota (38).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, in recent years, the effect of non-caloric sweeteners on the regulation of glucose levels has also been evaluated. The results to date are controversial, finding that some artificial sweeteners induce glucose intolerance (37). This may be due to the type of noncaloric sweetener consumed, its absorption and transport in the small and large intestines, as well as shifts in gut microbiota (38).…”
Section: Discussionmentioning
confidence: 99%
“…Diet can rapidly alter the gut microbiome community in as short as 24 h (David et al, 2014). For example, many laboratory studies of adult rodents have shown that a typical Western diet (high in fat and sugar) alters the gut microbiome community and reduces diversity of bacterial species (Becker et al, 2020;Beilharz et al, 2017;Leamy et al, 2014;Pindjakova et al, 2017;Turnbaugh et al, 2008). In multiple strains of inbred, outbred and transgenic mice, a shift in diet can have lasting effects on the community, as repetitive switching from a high-fat, high-sugar diet to a low-fat diet results in altered community membership and composition that does not revert to the original state (Carmody et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Also, Rosales-Gómez et al (2018) showed that stevia has increased glycaemia and the HOMA index, evidencing insulin resistance, in healthy mice. Also, Becker et al (2020) showed that stevia changed the gut microbiota as did saccharin when consumed with a high fat diet.…”
Section: Discussionmentioning
confidence: 99%